THE GENERAL CONCEPT OF ABILITY AND STAGES OF ITS DEVELOPMENT (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article provides information about the general definition of abilities, their types and stages of development, as well as the views of scientists from different periods on abilities.